USING WORKING MEMORY AND DEVELOPING CRITICAL THINKING IN THE REFLECTIVE LEARNING AND TEACHING PROCESSES - Martínes Gómez, Jhon Jairo (Caminos educativos, 2019)
This paper attempts to provide reflection upon day to day teaching exercise and proposes a methodological procedure to engage students thru working memory and critical thinking development in the target language during the learning process. It suggests a procedural method consisting on Programming Units, Physical Responses, and Transition to Behavior (PURF, TPR & T2B) to meet Bloom´s taxonomy accordingly. It also refers to the role of the EFL teacher as a facilitator who uses a wide variety of resources including technology; similarly the active role of the learner framed within experiential learning theory is mentioned.